Citreicella aestuarii sp. nov., isolated from a tidal flat - Park, Moon Su; Chung, Bok-Sil; Lee, Hyo Jung; Jin, Hyun Mi; Lee, Sang-Suk; Oh, Young Kyoon; Jeon, Che Ok (International Journal of Systematic and Evolutionary Microbiology, 2011)
A Gram-negative bacterium, designated AD8T, was isolated from a tidal flat of the Taean coast in South Korea. Cells were strictly aerobic, motile, ovoid rods or rods, with two lateral flagella on one side. Strain AD8T was catalase- and oxidase-positive and able to oxidize thiosulfate and reduce nitrate to nitrite. Growth of strain AD8T was observed at 15–40 °C (optimum 25–30 °C), at pH 5.0–9.5 (optimum pH 6.0–7.5) and with 1.0–11.0 % (w/v) NaCl (optimum 2.0–4.0 %). The predominant fatty acids were C18 : 1ω7c and C19 : 0 cyclo ω8c. The G+C content of the genomic DNA was 67.5 mol% and the major quinone was Q-10. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain AD8T belonged to the genus Citreicella and was most closely related to Citreicella marina CK-I3-6T within the class Alphaproteobacteria (96.9 % 16S rRNA gene sequence similarity). On the basis of phenotypic, chemotaxonomic and phylogenetic analysis, strain AD8T represents a novel species within the genus Citreicella, for which the name Citreicella aestuarii sp. nov. is proposed. The type strain is AD8T ( = KACC 13699T = DSM 22011T).